IT-Architecture Study Literature Research Collaboration: Malay Architecture Context - Gun Faisal; Nina Fadilah Najwa; Muhammad Ariful Furqon; Fazrol Rozi (Society of Visual Informatics, 2021)
Talking about architecture culture means talking about buildings and architecture. Architecture is a field of research that is always related to space and form. One of the exciting research topics on architecture is research on Malay architecture. Preserving Malay architecture is an important thing that must be done physically and meaningfully, positively impacting the community's development. The rapid development of information technology (IT) should be part of conservation efforts. IT supports various activities that significantly help conservation efforts. The role of IT in architecture is a significant research opportunity because of still little research on this topic. Thus, we conduct a study and analysis using a systematic literature review methodology to review IT-Architecture research, especially Malay architecture. The systematic literature review methodology consists of six stages, namely: (1) research question definition; (2) literature searching by keywords on literature sources; (3) literature assessment; (4) literature quality measurement; (5) data extraction and synthesis; and (6) research recommendation and suggestion. After going through the quality assessment process, only 37 papers were obtained that were relevant to the topic of IT-Architecture. The most discussed research themes in this literature review search were: (1) building information modeling (BIM) and augmented reality (AR) / virtual reality (VR); (2) BIM and geographic information system (GIS); and (3) BIM application and technology. However, based on literature searches, IT, and Malay architecture are still insufficient. Therefore, the topic of IT and Malay architecture still needs to be studied further in the future.